Teacher education curriculum for biomedical electronics technology education - (:unkn) unknown (IEEE, Piscataway, NJ, United States, 1999)
Biomedical equipment technology and technician schools always fall short of teachers to teach biomedical equipment technology courses. For this reason, a teacher education program for biomedical electronics technology has been designed and developed.